An Inventory Model with Partially Time-Varying Demand and Dynamic Cost Analysis - Tomar, Neeraj Kanak (Journal of Research in Vocational Education, 2026)
In this inventory model, I examine the inventory model with time-dependent demand that does not include item deterioration. Only time and demand have an impact on inventory level fluctuations. This system does not take shortages into account either. This model analyzes the effects of various parameters on ordering and holding costs. Evaluating the overall cost and examining the substantial impact on profit is the primary goal of this model's research. Numerical considerations that illustrate the nature of the cost in relation to varying levels of parameter variation are used to validate the model.